Cyclosporine-Based Medicinal Products: A Comparative Analysis of Pharmacopeial Quality Requirements - A. N. Novichenko; V. V. Akopova; P. A. Onisko (Regulatory Research and Medicine Evaluation, 2026)
INTRODUCTION . Cyclosporine is an immunosuppressive agent used in organ trans plantation, for the treatment of autoimmune diseases, and also in ophthalmology. Cyclosporine-based medicinal products (MPs) are registered in the Russian Fede ration in various dosage forms (DFs); the most widely used are “capsules” and “oral solution”. Since the State Pharmacopoeia of the Russian Federation (SP RF) does not include pharmacopeial monographs for the pharmaceutical substance (PS) and DFs of cyclosporine, it is relevant to conduct a comparative analysis and summarize the requirements of foreign pharmacopeias regarding the control of their quality. AIM . To perform a comparative analysis and summarize the requirements of foreign pharmacopeias for the quality of cyclosporine-based medicinal products (selection of quality attributes, regulatory requirements, and analytical methods) in order to prepare recommendations for drafting a national pharmacopeial monograph for the pharmaceutical substance cyclosporine and for developing corresponding specifications for cyclosporine-based medicinal products in the dosage forms “cap sules” and “oral solution”. DISCUSSION . To define the pharmacopeial quality standards for the PS of cyclospo rine, the current monographs of the European Pharmacopoeia (Ph. Eur.), British Phar macopoeia (BP), United States Pharmacopeia (USP), Indian Pharmacopoeia (IP), Phar macopoeia of the People’s Republic of China (ChP), International Pharmacopoeia (IntPh), and Japanese Pharmacopoeia (JP) were analyzed; for the DFs of cyclosporine, the monographs included in the USP, IP, BP, and ChP were analyzed. As a result of the analysis, the following attributes were identified for inclusion in the phar macopeial monograph for the PS of cyclosporine in the SP RF: “Description”, “Solu bility”, “Identification”, “Clarity of solution”, “Color of solution”, “Specific rotation”, “Related substances”, “Loss on drying”, “Bacterial endotoxins”, “Microbiological puri ty”, “Heavy metals”, “Sulfated ash”, and “Assay” along with their acceptance criteria and determination methods (infrared [IR] spectrometry, ultraviolet [UV] spectro metry, and high-performance liquid chromatography [HPLC]). Data on impurities (process-related impurities formed during fermentation; degradation products) and the control of their content in the PS of cyclosporine were summarized. Methods for the identification of the active substance in the DFs of cyclosporine (a combination of two methods, e.g., HPLC and thin-layer chromatography [TLC]) and for the assay of cyclosporine (HPLC) were determined; assay limits were established, as well as specific attributes requiring control: for the “capsules” DF, “Dissolution” and “Uni formity of dosage units”; for the “oral solution” DF, “Ethanol content” (if ethanol is used as a solvent), “Deliverable volume” (if a multidose package is used), and “Uniformity of mass (volume) of doses” (if a dosing device is used). CONCLUSIONS . Based on the results of the comparative analysis and summariza tion of the requirements of foreign pharmacopeias for the PS of cyclosporine and cyclosporine-based MPs in the DFs “capsules” and “oral solution”, recommendations were prepared for the development of a pharmacopeial monograph in the SP RF for the PS of cyclosporine and corresponding specifications for cyclosporine-based MPs in the DFs “capsules” and “oral solution”, covering identification methods, im purity limits, and the inclusion of other necessary attributes.